Int Adv Otol 2021
DOI: 10.5152/iao.2021.8124
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Venous Malformation With Secondary Aneurysmal Bone Cyst of Temporal Bone

Abstract: Aneurysmal bone cysts (ABCs) arising from vascular malformation are extremely rare, and none have been reported in the literature in English till now. We report a very rare case of secondary ABC of left temporal bone in a 5-year-old Caucasian boy who presented with a left sudden facial palsy associated with a painless non-tender mass of the left temporo-parietal region. The computed tomography (CT) and magnetic resonance imaging (MRI) features were suggestive of ABC secondary to a capillary venous malformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Observations A few cases of ABCs in the cranial bone have been reported, but very few past papers report ABC-like changes in the cranial bone that developed in association with neoplasms. 7,8 These associated neoplasms are commonly giant cell tumor, chondroblastoma, osteoblastoma, osteosarcoma, chondromyxoid fibroma, and fibrous dysplasia. Capillary venous malformation with ABC-like change in a 5-year-old boy 7 and a few ABC-like lesions associated with calvarial osteoblastomas have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations A few cases of ABCs in the cranial bone have been reported, but very few past papers report ABC-like changes in the cranial bone that developed in association with neoplasms. 7,8 These associated neoplasms are commonly giant cell tumor, chondroblastoma, osteoblastoma, osteosarcoma, chondromyxoid fibroma, and fibrous dysplasia. Capillary venous malformation with ABC-like change in a 5-year-old boy 7 and a few ABC-like lesions associated with calvarial osteoblastomas have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 These associated neoplasms are commonly giant cell tumor, chondroblastoma, osteoblastoma, osteosarcoma, chondromyxoid fibroma, and fibrous dysplasia. Capillary venous malformation with ABC-like change in a 5-year-old boy 7 and a few ABC-like lesions associated with calvarial osteoblastomas have been reported. [9][10][11] Gutierrez et al reported 49 cases of ABC-like lesions associated with primary neoplasms, regardless of location.…”
Section: Discussionmentioning
confidence: 99%